FITOSSOCIOLOGIA EM COMUNIDADES ARBÓREAS REMANESCENTES DE CERRADO SENSU STRICTO NO BRASIL CENTRAL - Finger, Zenesio; Finger, Felipe Augusto (Floresta, 2015)
Este estudo teve como objetivo caracterizar o estrato arbóreo das comunidades de cerrado sensu stricto mediante avaliações da riqueza, estrutura e diversidade. Os dados da vegetação foram obtidos empregando-se o método de parcelas múltiplas, com tamanho de 20 x 20 m (400 m2). Em cada uma das 82 unidades amostrais foram obtidas a altura total e as circunferências de todas as plantas arbóreas com perímetro a 0,30 m do nível do solo (PAB) maior ou igual a 15,7 cm (DAB ³ 5,0 cm). A partir da parcela 60 (24.000 m2 da área amostrada) a curva estabilizou-se com a ocorrência de 106 espécies, distribuídas entre 81 gêneros e 36 famílias, indicando que a amostragem foi suficiente para caracterizar e avaliar as vegetações de cerrado sensu stricto estudadas. As espécies com maior VI foram: Qualea parviflora, Curatella americana, Davilla elliptica, Qualea grandiflora, Pterodon emarginatus, Lafoensia pacari, Diptychandra aurantiaca, Myrcia albo-tomentosa, Caryocar brasiliense, Byrsonima pachyphylla, Byrsonima coccolobifolia, Hymenaea stigonocarpa, Callisthene fasciculata, Luehea paniculata, Magonia pubescens, Terminalia argentea, Erythroxylum deciduum, Couepia grandiflora e Pouteria ramiflora. A diversidade da vegetação arbórea encontrada na área estudada foi de 4,033 nats/ind. pelo índice de Shannon e de 0,975 pelo de Simpson, indicando alta diversidade florística. Abstract Phytosociology of the arboreal communities remainders of sensu stricto cerrado in Central Brazil. This study has a objective to characterize the cerrado sensu stricto communities’ arboreal stratum by evaluations of the richness, structures and diversity. Data of vegetation were obtained by the method of multiple plots, with size of 20 x 20 m (400 m2). In each one of the 82 patternless units were obtained the total height and the circumferences of all the arboreal plants with perimeter to 0.30 m from the level of the soil (PAB) larger or equal to 15.7 cm (DAB 5.0 cm). From the plot 60 (24.000 m2 out of the area used as sample) the curve is stabilized with the occurrence of 106 species, distributed between 81 genera and 36 families, indicating that the sampling was enough to characterize and to evaluate the vegetations of cerrado sensu stricto studied. The species with larger VI were: Qualea parviflora, Curatella americana, Davilla elliptica, Qualea grandiflora, Pterodon emarginatus, Lafoensia pacari, Diptychandra aurantiaca, Myrcia albo-tomentosa, Caryocar brasiliense, Byrsonima pachyphylla, Byrsonima coccolobifolia, Hymenaea stigonocarpa, Callisthene fasciculata, Luehea paniculata, Magonia pubescens, Terminalia argentea, Erythroxylum deciduum, Couepia grandiflora and Pouteria ramiflora. The diversity from the arboreal vegetation found in the area being studied was of 4.033 nats/ind. considering the Shannon Index and of 0.975 considering the Simpson Index, representing a great floristic diversity. Keywords: Phytosociological structures; richness; diversity.